Persaingan Antar Pedagang Dalam Perspektif Etika Bisnis Islam : Studi Pasar Tradisional Keramat Tinggi Kecamatan Muara Bulian - Siraj Aiqan Zhorifi; Agustina Mutia; Agusriandi Agusriandi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
In today's digital era, the economy is a very important aspect for every human life in order to meet every need such as clothing, food and shelter. In Islam, every human being is encouraged to compete in trying, but Islam underlines that the intended effort should be in terms of goodness not the other way around which can plunge people into satanic acts. In this study the method used is a qualitative method. The informants in this study were eight traders and three buyers. The type of data used is primary data with data collection techniques in the form of observation, interviews and documentation. Checking the validity of the data is done by testing the internal validity (credibility), preparing a triangulation plan, identifying informants and participants. Based on the results of this study indicate that the competition between traders in the Keramat Tinggi Market, Muara Bulian District includes five principles, namely unity (unity), balance (fairness), free will, responsibility, and truth. Of the five principles, most of the business competition activities carried out by traders are in accordance with Islamic business ethics, although there are some traders who carry out unfair business competition and conflict with Islamic business ethics, namely traders with large capital, setting prices below the prices of other traders and there are Merchants who report that the quality is not in accordance with their merchandise with the aim of turning off other traders and can harm the buyer. In implementing the five principles of Islamic business ethics there are obstacles to the principle of responsibility because there are some traders who actually provide insurance or compensation to the buyer if there is a defect in the goods and also some do not provide insurance to the buyer if there is a defect in the goods. But this happens not for the sole reason of making a profit, but to minimize the losses that occur.